2012
DOI: 10.1248/cpb.60.385
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Inhibitory Activities of 8-(Substituted styrol-formamido)phenyl-xanthine Derivatives on Monoamine Oxidase B

Abstract: The design and synthesis of two series of 8-(substituted styrol-formamido)phenyl-xanthine derivatives are described. Their in vitro monoamine oxidase B (MAO-B) inhibition were tested and the effect of substituents on the N-7, phenyl and the substituted positions are discussed. It was observed that compound 9b displayed significant MAO-B inhibition activity and selectivity, fluorine substitution plays a key role in the selectivity of MAO-B inhibition, and the styrol-formamido group at position-3′ may enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…Their activity resultsi nraising dopamine levels but also inhibition of the production of neurotoxic hydrogen peroxidea nd 1methyl-4-phenylpyridin-1-ium. [61] Designing as caffold containingb oth moieties resulted in ag roup of cinnamamide compoundse xhibiting activity of MAO-B inhibitors.…”
Section: Mao-b Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their activity resultsi nraising dopamine levels but also inhibition of the production of neurotoxic hydrogen peroxidea nd 1methyl-4-phenylpyridin-1-ium. [61] Designing as caffold containingb oth moieties resulted in ag roup of cinnamamide compoundse xhibiting activity of MAO-B inhibitors.…”
Section: Mao-b Inhibitorsmentioning
confidence: 99%
“…Designing as caffold containingb oth moieties resulted in ag roup of cinnamamide compoundse xhibiting activity of MAO-B inhibitors. [61]…”
Section: Mao-b Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies [ 12 , 13 ], we have reported that a group of PX derivatives are potent inhibitors of monoamine oxidase B (MAO-B) which are known to possess antiparkinsonian properties [ 14 , 15 ]. Since xanthine derivatives such as caffeine, CSC and istradefylline ( Figure 1 ) have the ability to block A2AR, we speculated that PX derivatives ( Figure 2 ) might also have similar ability.…”
Section: Introductionmentioning
confidence: 99%